International R&D sourcing, innovation and firm age: The advantage of 'born-international sourcers'. (April 2023) - Asimakopoulos, Grigorios; Revilla, Antonio; Rodríguez, Alicia
Abstract: We study how international knowledge sourcing affects the innovation performance of firms of different ages (from inception to mature). Specifically, we analyze (i) the contribution of international R&D sourcing to product innovations having a high degree of novelty—i.e. products that are new to the market; and (ii) the moderating role of firm age in this relationship. In doing so, we contrast two arguments that have created a debate in the literature: One is that experience plays a key role in successfully managing the inherent complexity of offshoring; another is that firms internationalizing at an early stage enjoy the learning advantages of newness. Based on a panel of over 9000 firms based in Spain spanning from 2008 to 2016, our findings indicate that international R&D sourcing is positively related to product innovations having a high degree of novelty, and that firm age exerts a negative moderating effect on the international R&D sourcing-innovation relationship. These results allow us to conclude that the innovation benefits of internationalizing the acquisition of knowledge are greater for younger firms. We identify the advantage of firms performing international R&D sourcing during their early stages and introduce the concept of 'born-international sourcers', to identify firms that engage in international sourcing strategies from an early stage. Highlights: R&D offshoring has a positive effect on sales of products new to the market. Firm age exerts a negative and significant moderator effect in this relationship. Younger firms use the advantage of R&D offshoring to innovate better than older firms. The innovation advantages of 'born-international R&D sourcers' are identified.